2020
DOI: 10.3390/ijd1010001
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Gender Differences in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is one of the main causes of visual loss in individuals aged 20–64 years old. The aim of this study was to investigate, in a multicenter retrospective cross-sectional study, sex-gender difference in DR in a large sample of type 2 diabetic patients (T2DM). 20,611 T2DM regularly attending the units for the last three years were classified as having: (a) No DR (NDR), (b) nonproliferative DR (NPDR), or (c) preproliferative/proliferative DR (PPDR). DR of all grades was present in 4294 T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Moreover, our meta‐regression showed that the proportion of female patients of study populations is significantly correlated with lower DR prevalence among patients with newly diagnosed T2DM. This finding supports previous studies that suggest men show a higher prevalence of DR versus women, indicating that male sex per se might be a risk factor for DR development 97 . Our univariate meta‐regression analysis was unable to demonstrate a significant association between the mean age of patients and the prevalence of established DR in patients with newly diagnosed T2DM.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, our meta‐regression showed that the proportion of female patients of study populations is significantly correlated with lower DR prevalence among patients with newly diagnosed T2DM. This finding supports previous studies that suggest men show a higher prevalence of DR versus women, indicating that male sex per se might be a risk factor for DR development 97 . Our univariate meta‐regression analysis was unable to demonstrate a significant association between the mean age of patients and the prevalence of established DR in patients with newly diagnosed T2DM.…”
Section: Discussionsupporting
confidence: 88%
“…It was also found that male and females using DPP4I had a higher risk of incident diabetic retinopathy than SGLT2I users, but within each drug group, males had a higher risk than females. Epidemiology studies have recognised that the male gender is an independent risk factor for developing diabetic retinopathy (42). It was also found that males and females using DPP4I had a higher risk of incident diabetic retinopathy than SGLT2I users, but within the DPP4I group, males had a higher association within developing new diabetic retinopathy, whereas in the SGLT2I group women had a slightly higher association with developing new diabetic retinopathy ( Figure 2F ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that males and females using DPP4I had a higher risk of incident diabetic retinopathy than SGLT2I users, but within the DPP4I group, males had a higher association within developing new diabetic retinopathy, whereas in the SGLT2I group women had a slightly higher association with developing new diabetic retinopathy ( Figure 2F ). Epidemiology studies which found that male sex is an independent risk factor of the development of diabetic retinopathy ( Figure 2C ) (42). Potential reasons for this include alterations in ocular blood flow regulation mediated by sex hormones and inflammatory cytokine profiles variations due to sex, in particular oestrogen in women having a vasodilating effect and testosterone in men having a vasoconstrictive effect potentially worsening diabetic retinopathy (42, 43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Diabetes Mellitus is a heterogeneous primary disorder of carbohydrate metabolism with absolute insulin deficiency (Type 1) or relative insulin deficiency (type 2), resistance or both leading to hyperglycemia. 3 The South Asian region shares a major proportion of this worldwide burden of diabetes. The prevalence of diabetes ranges from 0.9% in Bangladesh to 21.2% in india.…”
Section: Introductionmentioning
confidence: 99%